Pilot Plant Studies Using Moringa Oleifera (Kacang Kelor) Seeds As a Primary Coagulant in Surface Water Treatment - Mohammed, Ahmed Hussien Birima (2001)
Many researchers have used Moringa oleifera (Kacang Kelor) as a primary coagulant, for water treatment. It can also be used as coagulant aid, and floc toughners to either supplement or replace alum, ferric salts and synthetic polymers. The present study involves use of a pilot plant constructed by the author to evaluate the efficiency of Moringa oleifera seeds (25 % extracted seed oil) in treating turbidity of surface water collected from a stream located beside the hydraulic laboratory in the Department of Civil Engineering Universiti Putra Malaysia. Two stages were involved in the preparation of the seeds for the test. The seed wings and coat were first removed and ground to powder using a domestic blender. The second stage was the extraction of 25 % of the seed oil using the Soxhlet. Like the normal water treatment plant, the pilot plant was operated under four stages: coagulation, flocculation, sedimentation and filtration (rapid sand filter). Both conventional treatment (CT) and direct filtration (DF) methods were considered in running the pilot plant tests. Pilot plant tests were carried out three hours per run over whole period of three months. The turbidity, pH, alkalinity and zeta potential as well as the filter head loss were monitored regularly (every 30 minutes) during the test run. Average percentage turbidity removal of 75.4, 88.0, and 96.9 % resulted by DF for the low, moderate and high initial turbidity respectively, whereas CT gave average turbidity removal of 43.9, 93.5, and 95.7 for the same initial turbidity. The optimum dosages 20 and 30 mg/l of Moringa olei/era was applied for low and moderate turbidity respectively whereas for the high turbidity the Moringa oleifera dosage was varied from 50 - 80 mg/l depending on the initial turbidity. One out of eleven trials for CT gave a residual turbidity after filtration lower than 5 NTU. This value agreed with Malaysian guideline of 5 NTU. Eight trials gave a residual turbidity ranged from 8 - 15 NTU, which falls within the WHO maximum level of 25 NTU. 3 trials out of 7 for DF gave a residual turbidity after filtration lower than 5 NTU whereas 4 trials gave a residual turbidity ranged from 6.6 - 11 NTU. Turbidity removal of DF was found to be better than that of CT. Moringa oleifera was found to have no significant effect on pH or alkalinity of the water. Zeta potential of the water was found to decrease after treatment. The maximum filter head loss at depth 40 em was found to be 24 em for CT. In the case of DF the maximum head loss at depth 40 em was found to be 29.3 em for an average turbidity of 230.4 NTU and 70.9 em for an average turbidity of 88.7 NTU. Therefore, oil extracted Moringa oleifera seeds was found to posses a great potential for coagulation as a primary coagulant for treating surface water.